The Fibonacci function is defined recursively like this:
fib(n) == if n=0 n=1 1 else fib(n-1)+fib(n-2) fi .
We prove this by true-for-less induction after eliminating
Thm* a,b:. CoPrime(a,b) (x,y:. ax+by = 1) .
So under the inductive hypothesis
k:. k<n (x,y:. fib(k)x+fib(k+1)y = 1)
we must show
a,b:. fib(n)a+fib(n+1)b = 1
(we changed binding variable names to avoid confusion).
Consider the two cases of how
If it takes the first branch and computes to
If
a,b:. fib(n)a+(fib(n)+fib(n-1))b = 1 ,
which reduces by algebraic rearrangement to showing
a,b:. fib(n-1)b+fib(n)(a+b) = 1 .
But applying our inductive hyp to
fib(n-1)x+fib(n)y = 1 , for somex andy ,
so using
fib(n-1)x+fib(n)(y-x+x) = 1 satisfies our goal.
QED
About: